Pengembangan Desa Wisata Taro berbasis digital marketing sosial media - Fajar, Ni Made Anggia Paramesthi; Diasa, I Wayan; Adiandari, Ade Maharini (Nur Science Institute, 2021)
Taro Village is one of the tourism villages that has the oldest history in Bali. This Taro Tourism Village is an old village in Bali that is rich in stories and cultural relics of the past. The existence of this village is closely related to the visit of a sacred person in the past from East Java to Bali around the 8th century. This Taro Tourism Village has green and beautiful nature. The cool air and the trees make the atmosphere shady. As well as residents' houses with the characteristics of traditional Balinese houses. Besides enjoying the natural atmosphere, the tourist village of Taro also has many cultural values that can be an interesting source of knowledge for visitors to the tourist village. However, along with the development of the times, the Taro Tourism Village began to experience a setback because of the many other tourist attractions that offered new